“Instagramable” : Simulation, Simulacra And Hyperreality on Instagram Post - Maria Febiana Christanti; Puri Bestari Mardani; Intan Putri Cahyani; Windhiadi Yoga Sembada (Ridwan Institute, 2021)
The relationship between social media and individuals is complex. Like how humans flock to form an 'instagramable' culture on Instagram. The author examines this complexity using the lens of Jean Baudrillard in writings on simulation and simulacra. Baudrillard's main argument is that nothing in our culture is